Fronteiras em discussão : pensando as interações entre ficção e documentário em Diários de motocicleta por meio da intermidialidade - Ebert, Sancler (2016)
The research aims to think over about the overlaps between fiction and documentary in the film The Motorcycle Diaries (2004) by Walter Salles, using intermediality as method. We will use the intermedial phenomena proposed by Rajewsky (2012) as methodologi cal tools, thinking about intermedial transposition, combination of media and intermedial references. So, it's possible think over what kind of reading instruction is been triggered by the film, from the perspective proposed by Odin (2012): fictivizante or documentarizante. Our interest here is to think how literature transposed into film triggers such statements, relating the use of an open script to the reality of filming and also considering the influences between fiction and documentary related to road movie. We also seek to understand instructions that the film gives to emulate the photo and refer to documentary photography in three black and white sequences and using archival footage in the end credits.